Application of calcium-rich mineral under nonwoven fabric mats and sand armor as cap layer for interrupting N and P release from river sediments - Hong, Seung Hee; Lee, Chang Gu; Park, Seong Jik (Environmental Science and Pollution Research, 2022)
This work investigates the applicability of thermally treated calcium-rich minerals (CRMs), such as sepiolite (SPL), attapulgite (ATT), and dolomite (DLM) to hinder the nitrogen (N) and phosphorus (P) release from river sediments. A non-woven fabric mat (NWFM) or a sand layer were also capped as armor layers, i.e., placed over CRMs to investigate the capping impact on the N/P release. The capping efficiency was evaluated in a cylindrical reactor, consisting of CRMs, armor layers, sediments, and sampled water. We monitored N/P concentrations, dissolved oxygen (DO), oxidation reduction potential, pH, and electric conductivity in overlying water over 70 days. The DO concentrations in the uncapped and capped conditions were preserved for 30 days and 70 days (until the end of experiment duration), respectively. ATT showed higher efficiency for NH4-N and T-N than the other two materials, and the capping efficiency of NH4-N was measured as 96.4%, 93.7%, and 61.6% when capped with 2-cm sand layer, 1-cm sand layer, and NWFM layer, respectively. DLM showed a superior rejection capability of PO4-P to ATT and SPL, reported as 97.2% when capped with 2-cm sand armor. The content of weakly adsorbed-P was lower in the uncapped condition than in the capping condition. It can be concluded that ATT and DLM can be used as capping agents to deactivate N and P, respectively, to reduce water contamination from sediments of the eutrophic river.
Keywords: Calcium; Geologic Sediments; Minerals; Phosphorus; Rivers; Sand; Water; Water Pollutants, Chemical; Calcium; Clay mineral; In situ capping; Nitrogen; Phosphate; Sediment